Income inequality of households in Poland: A subgroup decomposition of generalized entropy measures - Muszyńska, Joanna; Wędrowska, Ewa (Nierówności dochodowe gospodarstw domowych w Polsce: dekompozycja miar uogólnionej entropii, 2018)
A formula of measures applied to assess the level of income inequality results from the intellectual basis on which this approach is founded. Our paper focuses on Generalized Entropy measures. The aim of our paper is two-fold. Firstly, it aims at presenting GE measures and discussing their properties, especially the property of additive decomposition. Secondly, the empirical aim is to assess the level of income inequality in Poland and to indicate its main determinants. In the study we use microdata obtained from EU-SILC that cover information about incomes received by individual household members in 2016. Five factors are chosen as the possible drivers of income inequality. The study proves the characteristics related to human capital are the most influential factors of income variability between households. The characteristics describing the composition of the household contribute to the overall level of inequality to a smaller extent.
Econometrics = Ekonometria, 2018, Vol. 22, No. 4, s. 43-64
Keywords: income inequality; General Entropy measures; decomposition